Analisis Proporsi Batuan Alami Sebagai Agregat Kasar Pada Asphalt Concrete (AC) Terhadap Karakteristik Marshall Dan Nilai Struktural - Mudigdyo, Ambar, Ir. Agus Riyanto MT (2017)
Aggregate gradation greatly affect the quality of pavement AC-BC, to control the particles aggregate to conform to spesifikisi then performed with stone crusher aggregate processing. In the treatment process not infrequently encountered an aggregate that has been processed is still mixed with natural rock that does not have a broken field. Natural rock will lower interlocking system, resulting in friction between the granular aggregate, which would degrade the quality of the pavement. Therefore this study aims to determine the effect of natural rock and the maximum proportion of natural rock in the mix AC-BC in terms of characteristics and value Structural Marshall. this study used an experimental method based on the guidelines according to SNI 06-2489-1990 and Highways 2010 General Specification Revision III. Begins with an examination of the materials used and compile aggregate grading as the composition of the mixture. Then make Marshall specimens for testing Phase 1 using aggregate as a raw material to determine the optimum bitumen content (OBC) on the variation of bitumen content of 4.5% 5% 5.5% 6.5% 6% 7% of the total aggregate characteristics were evaluated in Marshall , Based KAO then make Marshall specimens for Phase II testing using natural rock as a partial replacement of coarse aggregate with a variation of 10% 20% 30% 40% of the total coarse aggregate, in terms of characteristics and value Structural Marshall. The results showed that natural rock did lower quality mix AB-BC in terms of characteristics and value Structural Marshall at OBC 5.65%. Only on natural rock variation of 0% and 10%, which meets the specifications of Highways 2010 Revision III. The greater the level of natural rock value stability tends to be down, and the value of VMA further, to the value of Flow and VIM has increased to reach the maximum limit of the specifications of the levels of natural rock 20%, the value VFWA and Marshall Quotient tends to fall to reach the minimum specifications of levels natural rock 30%. For natural rock optimum proportion is 5% of the total coarse aggregate, but up to 10% levels of natural rock can still produce a mixture that meets specifications. For structural value greater levels of natural rock Structural Values getting smaller